The Contract of the Social Security Agency for Employment (BPJS Ketenagakerjaan) in The Perspective of Sharîa Economic Law - bahjatul imaniyah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2019)
In providing social security, the government requires all Indonesian workers to become members of the BPJS Employment. However, because the majority of the population is Muslim who live based on the laws of the Qur'an and Sunnah, it is necessary to review whether the BPJS Employment has fulfilled the syarî'ah economic law or not. By applying the method of normative legal research and interview techniques to parties concerned, this study concludes that the contract of the BPJS Employment program does not deviate from the sharia economic law (Islamic economic law) because, in the compensation on accident during the work program (JKK) it can be categorized as tabarru’ contract which only applies to virtue. The Death Insurance program (JKM) is an implementation of at-takmin at-ta’âwuniy, which is ta’âwun in a tabarru’ conrract.  As for the Old Age security program (JHT), it’s concept is similar to the contract of mudlârabah musytarakah. The same goes for the Pension Insurance (JP) program as a transition from the contract for wârits.